Life cycle assessment of the sustainability of bridges: methodology, literature review and knowledge gaps - Milić, Ivana; Bleiziffer, Jelena (Frontiers in Built Environment, 2024)
Analysing the entire project life cycle is a new trend in sustainability assessment in the construction sector. Research on sustainability issues in the construction sector started with issues related to buildings, while research for other structures such as infrastructure projects and bridges was not originally an integral part of the research. Therefore, the findings, knowledge and practical applications for buildings are more comprehensive than for infrastructure projects. This paper deals with the assessment of the sustainability of bridges throughout their life cycle and emphasises the importance of life cycle analysis of bridges in the early stages of planning and design. The study provides an overview of existing life cycle sustainability assessment (LCSA) methodologies for environmental (Life Cycle Assessment - LCA), economic (Life Cycle Cost - LCC) and social (Social - Life Cycle Assessment – S-LCA) aspects. This paper provides a critical overview of the current state of the art in the field of LCSA of bridges. To identify knowledge gaps, a review of the literature on LCSA of bridges, which performs a comparative life cycle analysis of different variants or components of the load-bearing structure of bridges is provided. The main objective of the paper is to provide recommendations for conducting LCSA of bridges and to identify research directions for design criteria for sustainable bridges of the future.